Rats and humans differ in processing collinear visual features - Meier, Philip M.; Reinagel, Pamela (Frontiers in Neural Circuits, 2013)
Behavioral studies in humans and rats demonstrate that visual detection of a target stimulus is sensitive to surrounding spatial patterns. In both species, the detection of an oriented visual target is affected when the surrounding region contains flanking stimuli that are collinear to the target. In many studies, collinear flankers have been shown to improve performance in humans, both absolutely (compared to performance with no flankers) and relative to non-collinear flankers. More recently, collinear flankers have been shown to impair performance in rats both absolutely and relative to non-collinear flankers. However, these observations spanned different experimental paradigms. Past studies in humans have shown that the magnitude and even sign of flanker effects can depend critically on the details of stimulus and task design. Therefore either task differences or species could explain the opposite findings. Here we provide a direct comparison of behavioral data between species and show that these differences persist -- collinear flankers improve performance in humans, and impair performance in rats -- in spite of controls that match stimuli, experimental paradigm, and learning procedure. There is evidence that the contrasts of the target and the flankers could affect whether surround processing is suppressive or faciliatory. In a second experiment, we explored a range of contrast conditions in the rat, to determine if contrast could explain the lack of collinear facilitation. Using different pairs of target and flanker contrast, the rat’s collinear impairment was confirmed to be robust across a range of contrast conditions. We conclude that processing of collinear features is indeed different between rats and humans. We speculate that the observed difference between rat and human is caused by the combined impact of differences in the statistics in natural retinal images, the representational capacity of neurons in visual cortex, and attention.